La racematio in Seneca apoc. 2, 1 e Marziale 3, 58, 8–9: (con qualche riflessione sulle varie forme di spigolamento dall’antichità ai giorni nostri) - Grazzini, Stefano (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XL-XLI (2004-2005). At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.